Breast Cancer Cytochromes P450: Chemopreventive and/or Therapeutic Targets for Naturally Occurring Phytochemicals - Hanna Szaefer; Barbara Licznerska; Hanna Sobierajska; Wanda Baer-Dubowska (Molecules)
Estrogens are considered the most important risk factor for the development of breast cancer. Therefore, attempts are being made to reduce their level through diminished synthesis on one hand and to protect against the formation of DNA-damaging estrogen metabolites on the other. Cytochromes P450 (CYPs) play key roles in estrogen synthesis and catabolism, leading to potentially carcinogenic metabolites. CYP19 (aromatase) catalyzes the conversion of androgens to estrogens. The estrogen receptor-dependent pathway induces cell growth. CYP1 family enzymes, particularly CYP1B1, are involved in the redox cycling of estrogen metabolites and the subsequent estrogen–DNA adducts formation. Naturally occurring phytochemicals of different classes were shown to modulate the CYP expression and activity in cell-free systems or breast cancer cells. One of the most promising CYP19 inhibitors is chrysin (flavone), while stilbenes seem to be the most effective CYP1B1 inhibitors. In most cases, their effect is not specific. Therefore, different approaches are made to find the best candidate for the drug prototype of a new therapeutic or chemopreventive agent and to improve its pharmacokinetic parameters. This review presents and discusses the possible effects on major CYPs involved in estrogen metabolism by phytochemicals from the most investigated classes, namely flavonoids, stilbenes, and glucosinolates breakdown products.